Acoustic wave sensors theory, design, and physico-chemical applications - Ballantine, David Stephen (Applications of modern acoustics)
Written by an interdisciplinary group of experts from both industry and academia, Acoustic Wave Sensors provides an in-depth look at the current state of acoustic wave devices and the scope of their use in chemical, biochemical, and physical measurements, as well as in engineering applications. Because of the inherent interdisciplinary applications of these devices, this book will be useful for the chemist and biochemist interested in the use and development ofthese sensors for specific applications; the electrical engineer involved in the design and improvement of these devices; the chemical engineer and the biotechnologist interested in using these devices for process monitoring and control; and the sensor community at large. Key Features * Provides in-depth comparison and analyses of different types of acoustic wave devices * Discusses operating principles and design considerations * Includes table of relevant material constants for quick reference * Presents an extensive review of current uses of these devices for chemical, biochemical, and physical measurements, and engineering applications.